2021
DOI: 10.1161/atvbaha.120.315556
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes Induce Mitochondrial DNA Damage and Trigger TLR9 (Toll-Like Receptor 9)-Mediated Atherosclerosis

Abstract: Objective: Electronic cigarette (e-cig) use has recently been implicated in promoting atherosclerosis. In this study, we aimed to investigate the mechanism of e-cig exposure accelerated atherosclerotic lesion development. Approach and Results: Eight-week-old ApoE −/− mice fed normal laboratory diet were exposed to e-cig vapor (ECV) for 2 hours/day, 5 days/week for 16 weeks. We found that ECV exposure significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 71 publications
0
43
0
Order By: Relevance
“…Our previous studies described that e-cig exposure can induce oxidative stress in the mitochondrion and dysregulation of mitochondrial complexes in lung fibroblasts [39]. Furthermore, e-cig exposure causes an increased amount of damaged mitochondrial DNA in plasma as well as increases the risk of cardiovascular diseases [18]. In this study, we showed that most of the TCA cycle-related metabolites are downregulated in e-cig users while there were no changes in the cigarette smokers compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies described that e-cig exposure can induce oxidative stress in the mitochondrion and dysregulation of mitochondrial complexes in lung fibroblasts [39]. Furthermore, e-cig exposure causes an increased amount of damaged mitochondrial DNA in plasma as well as increases the risk of cardiovascular diseases [18]. In this study, we showed that most of the TCA cycle-related metabolites are downregulated in e-cig users while there were no changes in the cigarette smokers compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that e-cig vaping and cigarette smoking inhibited bioenergy synthesis and induced mitochondrial dysfunction [15,16]. Mitochondrial metabolism alternation in lungs was followed by cigarette smoke exposure [15,16]; e-cig exposure induced mitochondrial oxidative stress and DNA damage [17,18]. Interestingly, a previous study explained that circulated PG would be metabolized into lactic acid in the liver and go through the TCA cycle [19].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, macrophage-mediated inflammation and matrix remodeling promote further epithelial dysfunction, resulting in a positive feedback loop in which inflamed and damaged tissues release chemotactic signals that further recruit monocytes from the blood to the area of insult. Macrophages and monocytes also mediate dysfunction in the interior of blood vessels by promoting the development of ECA-induced atherosclerotic plaques via toll-like receptor 9 activation; blockade of this receptor ameliorated the production of inflammatory cytokines in the plasma [113].…”
Section: Macrophagesmentioning
confidence: 99%
“…A series of mouse model experiments [ 8–10 ] showed that the mtDNA damage affected lipid metabolism. For instance, the damaged mtDNA promoted lipid deposition in the atherosclerotic plaque [ 8 ], while the mtDNA dysfunction induced dyslipidemia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A series of mouse model experiments [ 8–10 ] showed that the mtDNA damage affected lipid metabolism. For instance, the damaged mtDNA promoted lipid deposition in the atherosclerotic plaque [ 8 ], while the mtDNA dysfunction induced dyslipidemia [ 9 ]. Moreover, the loss of mitochondrial polymerase-γ proofreading activity (PolgD257A/D247A) and ApoE knockout (ApoE −/− ) caused severe dyslipidemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%